Pecuniary knowledge externalities in a new taxonomy: Knowledge interactions in a vertically integrated system - Agnieszka Gehringer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
The paper presents a new sectoral taxonomy that focuses on the existence of non negligible external effects, deriving from user-producer knowledge interactions, the latter in turn coupled with intermediate goods transactions, in a system of vertically integrated manufacturing and services sectors. These externalities, the so called pecuniary knowledge externalities, are the main source of changing technological conditions experienced by downstream producers. A distinguishing feature of the taxonomy consists, thus, in being derived from a particularly dynamic contexts of changing production functions. The taxonomy is obtained from an empirical exercise, examining effects generated by idiosyncratic knowledge in a system of input-output intermediate transactions between sectors in the European economy. The results permit to classify sectors in five groups, confirming the previous evidence of relevant differences in technological characteristics among sectors.
Keywords: 330; Pecuniary knowledge externalities; Sectoral patterns; Vertical linkages; Wissenstransfer; Lieferanten-Kunden-Beziehung; Branche; Klassifikation; Innovation; Panel; Schätzung; Europa